2017
DOI: 10.1002/jat.3443
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylated nanodiamonds can be used as negative reference inin vitronanogenotoxicity studies

Abstract: Nanodiamonds (NDs) are promising nanomaterials for biomedical applications. However, a few studies highlighted an in vitro genotoxic activity for detonation NDs, which was not evidenced in one of our previous work quantifying γ-H2Ax after 20 and 100 nm high-pressure high-temperature ND exposures of several cell lines. To confirm these results, in the present work, we investigated the genotoxicity of the same 20 and 100 nm NDs and added intermediate-sized NDs of 50 nm. Conventional in vitro genotoxicity tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…As regards their toxicity, ND are considered as the most biocompatible among the carbonaceous nanomaterials [10,11]. Indeed, carboxylated nanodiamonds were recently proposed as a negative control for nanogenotoxicity studies according to regulatory tests [12]. Besides drug delivery, bioimaging and biosensing, considered as the major bioapplications developed so far for ND [13], radiotherapy has to be added to the list since the pioneering work of Grall et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…As regards their toxicity, ND are considered as the most biocompatible among the carbonaceous nanomaterials [10,11]. Indeed, carboxylated nanodiamonds were recently proposed as a negative control for nanogenotoxicity studies according to regulatory tests [12]. Besides drug delivery, bioimaging and biosensing, considered as the major bioapplications developed so far for ND [13], radiotherapy has to be added to the list since the pioneering work of Grall et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…Today small NDs (4–10 nm) are synthesized in large quantities at a relatively low cost by detonation methodology and are the most frequently experimented in the biological and medical application. In vitro and in vivo animal studies, including oral, subcutaneous, intramuscular and intravenous administration, demonstrated the absence of genotoxicity cytotoxicity, biocompatibility, and non‐toxicity of nanodiamonds …”
Section: Introductionmentioning
confidence: 99%
“…Opposite results were reported by Moche et al [27] who conducted the research on HBE14 bronchial epithelial cell lines and T84 colon cancer cells. NDs of various diameters of 20, 50 and 100 nm was added to the medium and cells were incubated for 4 h. DNA damage was assessed using a comet test and a micronucleus test.…”
Section: Unfavorable Effects Of Carbon Nanoparticlesmentioning
confidence: 55%
“…Nanodiamonds (NDs) are tiny diamond crystals only a few nanometers in diameter, composed of carbon atoms arranged regularly ( Figure 1 C). They show exceptional hardness and excellent wear resistance [ 27 , 28 , 29 ]. Compared to fullerenes and nanotubes, NDs have a rough surface which facilitates their adhesion to other molecules.…”
Section: Characteristics Of Fullerenes Nanotubes and Nanodiamondsmentioning
confidence: 99%